Convoy commanders and other military identities in tomb art of Western Anatolia around the time of the Persian Wars - Draycott, C (Ministero per I Beni e le Attivita Culturalia, 2010)
This paper considers the emergence of various military guises in the tomb art of Western Anatolia as responses to the Persian Wars. It includes the convoy in the Tatarli Tomb, taken by others to be a funerary procession, as well other images of battle and warriors. The guises selected offer some insight into the cultural identities of the different communities of Western Anatolia during what is argued to be a formative period for politics, group identities and art.